2011
DOI: 10.1590/s0006-87052011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de orquídea em substratos à base de casca de café

Abstract: A utilização de resíduos agrícolas como substrato é uma alternativa promissora no cultivo de orquídeas, reduzindo os custos e o acúmulo desses materiais no ambiente. O objetivo do trabalho foi avaliar o desenvolvimento de orquídea híbrida (C. forbesii x C. labiata) x C. labiata em substratos à base de casca de café. O delineamento experimental utilizado foi o inteiramente casualizado, com seis tratamentos (xaxim desfibrado; casca de café; casca de café + coco em pó; casca de café + fibra de coco; casca de café… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
13
1
7
Order By: Relevance
“…Furthermore, commercial substrates usually have some fertilizer added in the mixture. These results contrast those found by Assis et al (2011), which observed greater averages for coffee bark mixtures with coconut coir and carbonized rice husk in orchid cultivation. Table 3 presents the results of the emergence speed index.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, commercial substrates usually have some fertilizer added in the mixture. These results contrast those found by Assis et al (2011), which observed greater averages for coffee bark mixtures with coconut coir and carbonized rice husk in orchid cultivation. Table 3 presents the results of the emergence speed index.…”
Section: Resultscontrasting
confidence: 99%
“…Com o objetivo de avaliar o desenvolvimento de orquídea híbrida (C. forbesiix C. labiata) x C. labiata em substratos à base de xaxim desfibrado; palha de café; palha de café + coco em pó; palha de café + fibra de coco; palha de café + casca de pinus; palha de café + casca de arroz carbonizada, Assis et al (2011) afirmam que a palha de café possui teores de potássio mais elevados que os demais substratos, conforme também foi possível observar no presente estudo.…”
Section: Resultsunclassified
“…For commercial cultivation, using quality substrate, which supports the development of these flowering, becomes extremely important (Assis et al, 2010). However, orchids growth happens slowly (Suzuki et al, 2010), exposing the substrate for long periods to colonization by weeds such as Pilea microphylla (brilhantina), which affects seedlings development, increasing the cost of production and reducing their commercial value (Freitas et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%